Prosedur Penanganan Pemuatan Karet ke dalam Kontainer di PT Varuna Tirta Prakasya (Persero) - Simmi, Simmi; Satria, Satria; Merry Safrina (Badan Penerbit STIEPARI Press, 2025)
Proper logistics handling greatly affects the smooth distribution of export goods, including rubber commodities which are one of Indonesia's leading products. This report aims to systematically review and explain the procedure for handling the loading of rubber into containers at PT Varuna Tirta Prakasya (Persero) Palembang Branch. The methods used are direct observation and field studies to obtain factual data related to workflows, documentation, and obstacles faced during the loading process. The results of the study show that the company has implemented a structured loading procedure that includes stages ranging from receiving a Work Order (SPK), checking the condition of the container, checking rubber bales, loading process using forklifts, balanced loading arrangement, installation of official seals, to documentation and delivery to the port. This procedure is able to maintain the physical quality of the rubber, speed up the working time, and increase exporter satisfaction. However, several obstacles were also found in the field, such as delayed arrival of containers, weather disturbances, lack of tools and manpower, and lack of coordination between divisions. Therefore, increasing the effectiveness of coordination, procuring additional tools, and utilizing information technology are important recommendations in improving the quality of logistics services in the company.